2019
DOI: 10.1038/s41467-019-10261-6
|View full text |Cite
|
Sign up to set email alerts
|

Blimp1+ cells generate functional mouse sebaceous gland organoids in vitro

Abstract: Most studies on the skin focus primarily on the hair follicle and interfollicular epidermis, whereas little is known regarding the homeostasis of the sebaceous gland (SG). The SG has been proposed to be replenished by different pools of hair follicle stem cells and cells that resides in the SG base, marked by Blimp1. Here, we demonstrate that single Blimp1 + cells isolated from mice have the potential to generate SG organoids in vitro. Mimicking SG homeostasis, the outer layer of these o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…[ 28 ] Triglycerides, a component of sebum lipids, may undergo hydrolysis by microbial lipases generating FFAs. [ 29‐31 ] Thus, next we compared the composition of the FFAs in the sebum surrounding back skin hairs of both WT and APOE −/− mice to assess whether the sebum of APOE −/− mice was affected by the hypercholesterolaemic profile of these mice. The sebum FFA composition of WT and APOE −/− mice was overall comparable (Figure 4D), indicating that the observed differential response to hypercholesterolaemia between back and ear skin cannot be explained by effects on the FFA content of sebum.…”
Section: Resultsmentioning
confidence: 99%
“…[ 28 ] Triglycerides, a component of sebum lipids, may undergo hydrolysis by microbial lipases generating FFAs. [ 29‐31 ] Thus, next we compared the composition of the FFAs in the sebum surrounding back skin hairs of both WT and APOE −/− mice to assess whether the sebum of APOE −/− mice was affected by the hypercholesterolaemic profile of these mice. The sebum FFA composition of WT and APOE −/− mice was overall comparable (Figure 4D), indicating that the observed differential response to hypercholesterolaemia between back and ear skin cannot be explained by effects on the FFA content of sebum.…”
Section: Resultsmentioning
confidence: 99%
“…[50,63] Therefore, CD44 expression in sebocytes at the surface of spheroids is likely to reflect a proliferative and undifferentiated state of SZ95 cells, which is similar to that of basal cells associated with SG in vivo. The establishment of SG spheroids by Yoshida et al [50] was, indeed, a landmark development in the recent years and was currently developed further by Feldman et al [64] and Boonekamp et al, [65] who constructed mouse . Examination of sections double-labelled with antibodies to K7 and cornifin confirmed that these markers were not co-expressed (D-F) (from: [47] under permission).…”
Section: D Sg -Lik E S Pheroidsmentioning
confidence: 99%
“…Furthermore, patient-specific 3D culture models and SKP may open new perspectives in understanding the genetic basis of skin diseases and in a therapeutic context in the field of personalized medicine. [50,64,80] In the future, such 3D systems could be combined with new scaffold technologies [98] and microfluidic platforms [99] allowing precise control and measurement of different culture parameters.…”
Section: Con Clus Ionmentioning
confidence: 99%
“…In contrast to other omics-technologies including genomics [8], transcriptomics [19] and proteomics [20] metabolomics is rarely used for characterization of organoid models. Whereas protocols for cell culture metabolomics are well established [21], only a few studies captured the metabolome from organoids by using NMR [22] and targeted [23] or non-targeted [24][25][26] LC-MS based profiling. In terms of non-targeted metabolomic profiling, there is an acute lack of optimization studies addressing problems such as the required sample amount and sampling conditions.…”
Section: Introductionmentioning
confidence: 99%